Members’ participation, empowerment and sustainability of self-help groups in Kano City, Nigeria - Ibrahim, Abdul-Aziz (2014)
Community’s involvements in Self-Help Groups (SHGs) create an avenue for grass root development at the community level through local organizations that are associated with self-help activities. Therefore, SGHs are playing important role through which people participate in community development activities and making sure that various communities develop their own initiatives by themselves. Despite the potential of SHGs, there are certain factors that restrained the sustainability of these groups. In line with this, the study examined the relationship between group member’s participation, empowerment, member’s perception towards leadership and group cohesion, and sustainability of self-help groups. In addition, the study examined the moderating effect of member’s perception towards leadership on the relationship between participation and sustainability of self-help groups in Kano City, Nigeria. In this study, data was collected from 400 respondents, and a multistage cluster sampling techniques was applied to select the respondents from Selp Help Groups (SGHs) in four local government areas (LGAs) in Kano, Nigeria. Data was collected using structured questionnaire. The descriptive analysis, Pearson correlation and multiple linear regression were analyzed using SPSS version 20. The findings of this study revealed that, there is high level of participation and empowerment among the members of self-help groups in Kano City, Nigeria. The result from Pearson correlation shows that, there is significant positive moderate relationship between members level of participation and group sustainability (r = .327, p = .000). And also, there is significant positive relationship between group members participation in decision making (r = .318, p = .000), self-efficacy (r = .226, p= .000), self-esteem (r = .253, p = .000), perceived control (r = .152, p = .002), and sense of belonging among group members (r = .108, p = .030) and group sustainability. However, the analyses shown that, there is no significant relationship between group members knowledge and skills (r = .070, p = .160), and social interaction among group members (r = .080, p = .111) and group sustainability. Furthermore, the results of the multiple regression analysis which includes members perception towards leadership, group members level of participations, group members participation in decision making, group members self-efficacy, group members selfesteem, group members perceived control and sense of belonging among group members is significant (F (7,392) = 2.319, P = .005). Therefore, about 39.8% of variance in group sustainability was explained by the all the predictor variables entered into the regression model. The analysis shows that, all the independent variables were significantly contributed to self-elp group sustainability. Similarly, the hierarchical multiple regression revealed that, members perception towards leadership moderate the relationship between level of participation and participation in decision making, and self-help groups sustainability in city of Kano (based on the difference between R 2= .651 and ΔR2 = .658). With regards to this finding the researcher concluded that, community members’ involvement in self-help groups has leads to empowerment in the self-help group. This study is in line with the previous literature by indicating that, leadership effort has the highest significant contribution to the sustainability of the self-help groups. The researcher recommended that, communities that need to develop their capacities through grassroots organizations should adopt the concept of self-help group formation.